2014
DOI: 10.1016/j.jacc.2014.03.062
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lifelong Exercise “Dose” on Left Ventricular Compliance and Distensibility

Abstract: Background Sedentary aging has deleterious effects on the cardiovascular system, including decreased left ventricular compliance and distensibility (LVCD). Conversely, Masters level athletes, who train intensively throughout adulthood, retain youthful LVCD. Objectives To test the hypothesis that preservation of LVCD may be possible with moderate lifelong exercise training. Methods Healthy seniors (n = 102) were recruited from predefined populations, screened for lifelong patterns of exercise training, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
135
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(141 citation statements)
references
References 39 publications
6
135
0
Order By: Relevance
“…47,[49][50][51] Age-related decline in left ventricular compliance and diastolic function has been implicated in the development of HF, particularly HF with preserved ejection fraction. [52][53][54][55] In a recent study, Bhella et al 56 observed that high levels of lifetime exercise (ie, 4-5 times per week) were associated with more favorable left ventricular compliance. In contrast, there Figure 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47,[49][50][51] Age-related decline in left ventricular compliance and diastolic function has been implicated in the development of HF, particularly HF with preserved ejection fraction. [52][53][54][55] In a recent study, Bhella et al 56 observed that high levels of lifetime exercise (ie, 4-5 times per week) were associated with more favorable left ventricular compliance. In contrast, there Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…were no differences in left ventricular compliance between sedentary individuals and casual exercisers (ie, 1-2 times per week). 56 Thus, doses of PA in excess of current guideline recommendations may be required to achieve favorable changes in cardiac structure and function and to lower HF risk.…”
Section: Discussionmentioning
confidence: 99%
“…These molecular factors are likely related to cardiomyocyte hypertrophy, loss of cardiomyocytes with age, and/or increased cardiac fibrosis (Cornelissen et al 2010;Dutta et al 2012). Recently, Bhella et al (Bhella et al 2014) provided insight into how low doses of regular physical activity do not appear to be sufficient to prevent the decreased LV compliance commonly associated with cardiovascular disease. Limiting frequency of regular exercise is difficult with our longitudinal mouse model but does suggest a necessary exercise volume threshold necessary for positive cardiovascular alterations.…”
Section: Discussionmentioning
confidence: 99%
“…These data were confirmed in HFpEF: low cardiorespiratory fitness could be not only considered as an early stage marker but also a target for prevention, owing to the impact of exercise training on risk factor profile, on left ventricle structure and function, on myocardial strain pattern, and on vascular stiffness 19. It was calculated that 1 MET improvement in physical activity was associated with 17% reduction of HFpEF risk at a later age21 and that daily dynamic exercise for >30 min four or five times weekly over the course of a lifetime preserves left ventricle diastolic function 22…”
Section: Before Heart Failure Onset (Past): Exercise As a Tool For Prmentioning
confidence: 99%